2018
DOI: 10.1159/000488706
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Gland <sup>18</sup>F-FDG Uptake in Neurofibromatosis Type 1

Abstract: Purpose: To investigate thyroid gland characteristics on 18F-FDG positron emission tomography/computed tomography (PET/CT) imaging in patients with neurofibromatosis type 1 (NF1). Subjects and Methods: Thyroid gland characteristics of patients with a clinical diagnosis of NF1 who underwent 18F-FDG PET/CT imaging for the first time to distinguish benign neurofibroma from malignant peripheral nerve sheath tumor (MPNST) at our institution (n = 69) were compared to PET/CT imaging of sarcoidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…A few reports have concluded that PET/CT screening of NF1 patients would also be useful in detecting lesions other than nervous system tumors. In the analysis of FDG‐PET/CT performed on 69 NF1 patients focusing on thyroid, 4 NF1 patients were diagnosed with multinodular goiter, 2 with benign chronic lymphocytic thyroiditis, 1 with metastasis to the thyroid, and 1 with medullary thyroid cancer; 36 9 lesions other than neurogenic tumors were also found in the present study and 5 were thyroid diseases. It is also noteworthy that 3 of 9 lesions were malignant (1 liposarcoma and 2 GISTs) and required immediate surgical treatment, confirming that NF1 is a tumor predisposing syndrome.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A few reports have concluded that PET/CT screening of NF1 patients would also be useful in detecting lesions other than nervous system tumors. In the analysis of FDG‐PET/CT performed on 69 NF1 patients focusing on thyroid, 4 NF1 patients were diagnosed with multinodular goiter, 2 with benign chronic lymphocytic thyroiditis, 1 with metastasis to the thyroid, and 1 with medullary thyroid cancer; 36 9 lesions other than neurogenic tumors were also found in the present study and 5 were thyroid diseases. It is also noteworthy that 3 of 9 lesions were malignant (1 liposarcoma and 2 GISTs) and required immediate surgical treatment, confirming that NF1 is a tumor predisposing syndrome.…”
Section: Discussionsupporting
confidence: 60%
“…patients focusing on thyroid, 4 NF1 patients were diagnosed with multinodular goiter, 2 with benign chronic lymphocytic thyroiditis, 1 with metastasis to the thyroid, and 1 with medullary thyroid cancer; 36 9 lesions other than neurogenic tumors were also found in the present study and 5 were thyroid diseases. It is also noteworthy that Seventy-five pNFs in 28 patients with NFI were analyzed in a previous report, and the growth rate of pNF correlated significantly positively with SUVmax (P = .003).…”
Section: Discussionsupporting
confidence: 59%
“…Clinical presentation, notably age at diagnosis, does not seem to differ from the usual presentation. Differentiated thyroid cancer can be found through focal hypermetabolism on 18 FDG PET-CT that is initially performed to distinguish between neurofibromas and malignant peripheral nerve sheath tumors (185,186).…”
Section: Nf1mentioning
confidence: 99%
“…7,15 Thyroid morphology and function studied in 17 patients with NF-1 showed nodular goiter in 10 patients, and after those 10 patients have undergone thyroidectomy, thyroid cancer was found in 2 cases (11.76%), indicating that thyroid disease may be underestimated in the context of NF-1. 1,11 Although thyroid cancer is rarely reported in the literature, it might be detected incidentally in patients by ultrasonography especially when it is a small nodule, as the case reported by Bu Kyung Kim, which promotes the need for screening in NF-1 patients. 16,17 Precocious puberty was noticed in a 15-year-old boy who also had optic chiasm glioma and was diagnosed at the age of 6 years old.…”
Section: Resultsmentioning
confidence: 99%